Efficient electrospun terpolymer nanofibers for the removal of cationic dyes from polluted waters: A non-linear isotherm and kinetic study. Issue 4 (August 2021) - Altaleb, Hamud A.; Thamer, Badr M.; Abdulhameed, Meera Moydeen; El-Hamshary, Hany; Mohammady, Sayed Z.; Al-Enizi, Abdullah M.
Abstract: Most of the nanomaterials used as adsorbents are in powdered form, which in turn demands highly sophisticated techniques for separating them following the adsorption process. In this study, a series of novel terpolymers were prepared based on poly(sodium styrene sulfonate–co–acrylonitrile–co–styrene) P(SSAS) via solution-free radical polymerization. The synthesized terplymers were blended with polyacrylonitrile (PAN) and converted to nanofiber sheets by electrospinning technique and used as easily-handleable and effective nanoadsorbent. The terpolymers and terpolymer/polyacrylonitrile nanofibers (SSAS/PAN NFs) were characterized using Fourier-transform infrared spectroscopy (FTIR), Thermogravimetric analysis (TGA), Differential scanning calorimetry (DSC) and Scanning electron microscope (SEM). The TGA results indicated that the terpolymers feature a single glass transition (Tg) and that their values (82.32–111.34 ℃) are a function of the monomer ratio. Additionally, SEM images of the as-prepared SSAS/PAN NFs revealed a homogeneous and smooth morphology with diameters ranging from 529 to 947 nm, depending on the monomer ratio. Importantly, the prepared SSAS/PAN NFs exhibited powerful action as a nanoadsorbent for the removal of crystal violet (CV) dye from aqueous solutions across a wide pH domain and without further filtration/centrifugation processes being required. The measured adsorption capacity of different SSAS/PAN NFs for the removal of CV dye adhered to the following order: SSAS/PAN NFs-1 (439.85 mg/g) >SSAS/PAN NFs-2 (255.60 mg/g) and >SSAS/PAN NFs-3 (185.96 mg/g) >PAN NFs (85.43 mg/g), with SSAS/PAN NFs-1 having an adsorption capacity eight times higher than that of PAN NFs alone. The estimated thermodynamic parameters indicate that the adsorption of CV dye on the surface of SSAS/PAN NFs was a spontaneous and endothermic process. Ultimately, the obtained kinetic and thermodynamic results clearly attest to the fact that the investigated SSAS/PAN NFs offer a facile approach to the design of an efficient nanoadsorbent for the removal of cationic impurities from wastewater. Graphical Abstract: ga1 Highlights: Novel terpolymers were synthesized by simple route and converted to nanofibers by electrospinning technique. Prepared terpolymers used as powerful adsorbent for cationic dyes removal. Adsorption isotherm and kinetic was studied by nonlinear models. The adsorption mechanism was concluded as exothermic, spontaneous and favorable process.